THE EFFECT OF SONIC OSCILLATION ON THE STRUCTURE AND FUNCTION OF BEEF HEART MITOCHONDRIA - Stasny, John T. (The Rockefeller University Press, 1964)
Sonic treatment of mitochondria from beef heart results in a distribution of variously sized particles which can be fractionated by differential centrifugation. Electron microscopic observations of negatively stained fractions shows the presence of subunits, which are "knob-like" in appearance, attached to the mitochondrial membrane and membrane derivatives. Such subunits are not completely removed from the membrane by 5 minutes of sonic treatment. However, a fraction containing singular subunits of dimensions similar to those of units attached to the mitochondrial membrane has been observed. Enzymatic activities and cytochrome contents were determined for mitochondria and the fractionated, mitochondrial membrane derivatives. A concentration of enzyme activity and cytochrome content was found in fractions sedimented at 35,300 g and 79,420 g via differential centrifugation in 2x distilled water. The fraction with the highest enzymatic activities and cytochrome content, although rich in mitochondrial membrane derivatives, is deficient in membrane-bound subunits. The fraction with the lowest enzymatic activities and cytochrome content resembles detached mitochondrial subunits when examined in the electron microscope. The biochemical data and the electron microscopic observations suggest that the mitochondrial membrane and not the subunits are responsible for electron transport activity.